Wajah Indo dalam Iklan Tahun 1950an - Suwardikun, Didit Widiatmoko (PANGGUNG, 2016)
ABSTRACTÃÂ 1950s society in Indonesia ÃÂ was marked by the changing ÃÂ social ÃÂ class, at the ÃÂ time ÃÂ of the Dutch East Indies, indigenous groups or Ã¢â¬ÅinlanderÃ¢â¬Â ÃÂ as the lowest grade. After the independence war a large ÃÂ number ÃÂ of indigenous ÃÂ people shifted ÃÂ into ÃÂ top class. That changes ÃÂ was used ÃÂ to advertise ÃÂ the consumer ÃÂ goods of internationalÃÂ  ÃÂ campanies. ÃÂ How was the ÃÂ figure ÃÂ of ideal ÃÂ model advertised at that time? Through visual analysis ÃÂ on consumer ÃÂ goods advertisement ÃÂ in newspa- pers published in the 1950s as well as an interview to the resource person, it was found that the visualization ÃÂ of women as a model, were wearing ÃÂ Indonesian ÃÂ dress, but the structure ÃÂ of the face and physical proportions were western ÃÂ type. Admiration ÃÂ for the beauty ÃÂ of western ÃÂ valuesÃÂ  ÃÂ is used as a tool to persuade the target audience, indigenous on new high social class, the women of Indonesia, ÃÂ especially ÃÂ in West Java which is famous for the light-skinned girl and a beautiful face.ÃÂ Keywords : eurasian ÃÂ face, visual persuasion, advertisement.ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Dekade 1950an tatanan masyarakat di Indonesia ditandai dengan berubahnya kelas sosial, pada zaman Hindia Belanda, kelompok pribumi atau Ã¢â¬Åinlander Ã¢â¬Â sebagai kelas yang paling rendah, setelah perang kemerdekaan sejumlah besar orang pribumi bergeser menjadi kelas paling atas. Perubahan itu dimanfaatkan produsen untuk mengiklankan barang-barang konsumen produksi perusahaan internasional. Bagaimana figur ideal model iklan pada jaman itu? Melalui analisis visual pada iklan barang-barang konsumen di koran dan majalah yang diterbitkan pada tahun 1950an serta wawancara kepada narasumber, ditemukan bahwa visualisasi perempuan sebagai model iklan dengan cara berpakaian Indonesia, tapi struktur wajah dan proporsi tubuh bertipe Barat. Kekaguman terhadap nilai-nilai keindahan Barat digunakan sebagai alat untuk membujuk audiens target iklan, kelas sosial atas yang baru, para wanita Indonesia, khususnya di Jawa Barat yang terkenal dengan para gadis yang berkulit terang dan berwajah cantik.ÃÂ Kata kunci: wajah indo, persuasi visual, iklan koran.